Introspectiveness of Higher Education Students: Study and Development - Rerke, Viktoriya I. (2021)
The change in strategic guidelines in Russian education is associated with a revision of the goals of teaching and upbringing. However, the emphasis of reforms has shifted towards the formation of the required professional competences at this stage in the development of the education system of the Russian Federation. We think that it is possible to achieve the set goal of higher education through the development of the introspectiveness as a quality of the personality of students. The formation of the introspectiveness in a future specialist will have an effect on the successful mastery, expansion and transformation of social experience, as well as the internal plan of action. Thus, demonstrating the formed introspectiveness as a personality trait, the student is able to organize his educational activities independently, activities to cognize the surrounding reality and his inner world, as well as self-determine in various life situations, including the development of general cultural and professional competences. In this regard, the emphasis in the issue of developing the introspectiveness of students is made on specifying the conditions that must be created at a higher education institution for the manifestation and formation of this personality quality. The purpose of the article is to study the level of the introspectiveness of university students and develop psychological and pedagogical conditions that develop this personality quality. The leading techniques for the study of this problem were the following: Q-sort Technique; the technique for diagnostics of an individual measure of the introspectiveness degree. At the stage of the ascertaining experiment, the levels of the introspectiveness of university students were revealed. The results of the ascertaining experiment convincingly demonstrated the need to organize special work to develop the introspectiveness of students. The authors substantiated that the success of developing students’ introspectiveness is ensured by the created psychological and pedagogical conditions. A model of developing the introspectiveness as a personality quality of a future professional has been developed and tested. The results of this study create opportunities for further development of the problem in the context of the organization of lectures in the learning process for students of different courses and types of specialization. The article is intended for psychologists, tutors, education managers.